Neurologic Toxicity of Immune Checkpoint Inhibitors: A Review of Literature - Albarrán, Víctor; Chamorro, Jesús; Rosero, Diana Isabel; Saavedra, Cristina; Soria, Ainara; Carrato, Alfredo; Gajate, Pablo (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors have entailed a change of paradigm in the management of multiple malignant diseases and are acquiring a key role in an increasing number of clinical sceneries. However, since their mechanism of action is not limited to the tumor microenvironment, their systemic activity may lead to a wide spectrum of immune-related side effects. Although neurological adverse events are much less frequent than gastrointestinal, hepatic or lung toxicity, with an incidence of <5%, their potential severity and consequent interruptions to cancer treatment make them of particular importance. Despite they mainly imply peripheral neuropathies, immunotherapy has also been associated to an increased risk of encephalitis and paraneoplastic disorders affecting central nervous system, often appearing in a clinical context where the appropriate diagnosis and early management of neuropsychiatric symptoms can be challenging. Although the pathogenesis of these complications is not fully understood yet, the blockade of tumoral inhibitory signals, and therefore the elicitation of cytotoxic T-cell mediated response, seems to play a decisive role. The aim of this review is to summarize the current knowledge about the pathogenic mechanisms, clinical manifestations and therapeutic recommendations regarding the main forms of neurotoxicity related to checkpoint inhibitors.